Primary airway epithelial cell culture and asthma in children–lessons learnt and yet to come. Issue 12 (14th July 2015) - McLellan, Kirsty; Shields, Mike; Power, Ultan; Turner, Steve
Summary: Until recently the airway epithelial cell (AEC) was considered a simple barrier that prevented entry of inhaled matter into the lung parenchyma. The AEC is now recognized as having an important role in the inflammatory response of the respiratory system to inhaled exposures, and abnormalities of these responses are thought to be important to asthma pathogenesis. This review first explores how the challenges of studying nasal and bronchial AECs in children have been addressed and then summarizes the results of studies of primary AEC function in children with and without asthma. There is good evidence that nasal AECs may be a suitable surrogate for the study of certain aspects of bronchial AEC function, although bronchial AECs remain the gold standard for asthma research. There are consistent differences between children with and without asthma for nasal and bronchial AEC mediator release following exposure to a range of pro‐inflammatory stimulants including interleukins (IL)‐1β, IL‐4, and IL‐13. However, there are inconsistencies between studies, e.g., release of IL‐6, an important pro‐inflammatory cytokine, is not increased in children with asthma relative to controls in all studies. Future work should expand current understanding of the "upstream" signalling pathways in AEC, study AEC from children before the onset of asthma symptoms and in vitro models should be developed that replicate the in vivo status more completely, e.g., co‐culture with dendritic cells. AECs are difficult to obtain from children and collaboration between centers is expected to yield meaningful advances in asthma understanding and ultimately help deliver novel therapies.Pediatr Pulmonol. 2015; 50:1393–1405. © 2015 Wiley Periodicals, Inc.